Inclusive Development and Efforts to Improve Community Economy in Indonesia - Herman Deru; Kgs. M. Sobri; Alfitri Alfitri; Andries Lionardo (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: This study aimed to analyze the extent to which infrastructure development in Indonesia has a positive impact on an area, where the impact is not only seen from an economic perspective but also from a sociocultural and environmental perspective in the region. A systematic literature review was used as a method in this study to show various cases of infrastructure development and the impacts that occur in each of these development activities. Several cases from South Sumatra, East Kalimantan, East Nusa Tenggara, Sulawesi, and Papua were used in this paper to demonstrate the impact of inclusive and sustainable development on equity efforts in Indonesia comprehensively. The results of this study show a positive relationship between each case, where inclusive development can strengthen a region’s potential. Community involvement during and after development has a positive impact, either directly through the employment opportunities provided, or indirectly through economic potentials, such as post-development business development. Some factors to consider include the role of the government and development implementers in increasing community participation in all development activities in their area, where there are still some unresolved coordination issues.